Reconsideration of Secure Communities rollout reveals preemptive local-federal cooperation in immigration enforcement - Cesar D. Vargas Nunez; Sakshina Bhatt; Basil F. Seif; Fernando S. Mendoza; David D. Laitin; Asad L. Asad (Proceedings of the National Academy of Sciences, 2026)
Qualitative studies on local police collaborations with federal immigration enforcement authorities reveal risks to the well-being of noncitizens, particularly the undocumented, and their families and communities. Yet statistical evidence of these policies’ effects is mixed. We propose that quantitative studies may misidentify the timing of when these policies begin disrupting immigrant communities by relying on a policy’s formal enactment date to indicate its activation. We test this proposal in the context of Secure Communities, a federal program with a staggered rollout that asked local police to detain noncitizens they arrested for possible transfer into Immigration and Customs Enforcement (ICE) custody and deportation. Individual states signed a Memorandum of Agreement (MOA) with the federal government as a framework for their county-by-county activation of Secure Communities. Counties were not required to activate immediately; their formal enactment frequently occurred later when prompted by ICE. We find that the date when a state signed an MOA consistently predicts a county’s increased probability of receiving ICE requests to hold noncitizens in detention, transferring detained noncitizens into ICE custody, and removing noncitizens from the country. This relationship operates most strongly in counties with preexisting enforcement infrastructure between local police and federal immigration authorities. By contrast, while we find that enactment dates are associated with increases in each outcome, pretreatment trends render these relationships statistically indeterminate. Our results highlight how multilayered relationships between local and federal authorities allow for policing to be used as a tool for facilitating the preemptive implementation of immigration enforcement across the country at the expense of noncitizens and their families and communities.